Chapter 7: Pharmaceutical Toxicity (Principles of Medical Toxicology, 2025)
AuthorMrs. Rohini Koratana, Assistant Professor, Department of Pharmacology, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, IndiaAbstractPharmaceutical agents represent the most common causes of poisoning, with both intentional overdoses and therapeutic misadventures contributing significantly to morbidity and mortality. Analgesic toxicity varies widely by class, with acetaminophen causing delayed hepatotoxicity through toxic metabolite formation, while salicylates produce complex acid-base disturbances, hyperthermia, and multi-organ dysfunction. Opioid overdose presents with the classic triad of respiratory depression, miosis, and decreased consciousness, requiring prompt naloxone administration. Cardiovascular medication poisonings include beta-blocker and calcium channel blocker overdoses characterized by bradycardia, hypotension, and cardiogenic shock, often requiring high-dose insulin-euglycemia therapy or lipid emulsion treatment. Digoxin toxicity manifests with gastrointestinal symptoms, visual disturbances, and cardiac dysrhythmias responsive to specific antibody fragments. Among psychiatric medications, tricyclic antidepressant overdoses can cause life-threatening sodium channel blockade with QRS widening and seizures, while SSRI toxicity ranges from mild serotonin excess to life-threatening serotonin syndrome. Lithium's narrow therapeutic index leads to neurological toxicity with tremor, altered mental status, and seizures. Antimicrobial toxicities include aminoglycoside ototoxicity and nephrotoxicity, fluoroquinolone tendinopathies, and sulfonamide hypersensitivity reactions. Management principles emphasize toxin-specific interventions alongside supportive care tailored to the pharmaceutical agent's unique toxicokinetics and toxicodynamics.Keywords: Acetaminophen, Opioids, Cardiovascular Medications, Antidepressants, Antipsychotics, Antimicrobial ToxicityVIEW PDF